Family Burden in Caring for Family Members with Schizophrenia : A Systematic Review - Priyana Putra, Rausan Fikri (Universitas Aisyah Pringsewu, 2024)
Introduction Schizophrenia cases are increasing worldwide, especially in low- and middle-income countries. Schizophrenia is a serious and chronic mental illness that requires care for family members, but in practice, this becomes a burden for the family, both objective and subjective.Objective This systematic review aims to identify the main focus regarding the burden on families as caregivers of family members with schizophrenia.Method The research method uses PRISMA with a systematic approach and selection process with literature sources searched from the Scopus, PubMed, ScienceDirect, and ProQuest databases and manual searches with the keywords